The Relationship of Hematologic Parameters and Lipid Profile with Acute Ischemic Stroke - Sibel Canbaz Kabay; Fatma Akkoyun Arıkan; Dursun Ceylan; Merve Yatmazoğlu Çetin; Niyazi Uysal; Muhammed Alperen Bardakçı; Gönül Akdağ; Mustafa Çetiner; Emine Saygın Uysal (Sakarya Tıp Dergisi)
Objective: This study aims to investigate the effect of routine laboratory parameters on clinical outcomes in patients with acute ischemic stroke (AIS). Materials and Methods: Our study was designed as retrospective and cross-sectional. 94 patients with AIS who received inpatient treatment in our clinic with a diagnosis of acute ischemic stroke were included in the study. Laboratory data, demographic, and clinical characteristics were recorded at the time of admission. Neurological disabilities of the patients 3 months after treatment were evaluated with the modified Rankin Scale (mRS). mRS 0-2 was considered a good prognosis and mRS 3-6 was considered a poor prognosis. Results: Of the 94 patients included in the study, 47 were men and 47 were women. The mean age was 71.18±11.92 years. Laboratory parameters hemoglobin, eosinophil, totalcholesterol, ldl-cholesterol, and triglyceride values were significantly lower in the group with mRS≥3. As a result of ROC analysis, the area under the curve of hemoglobin, eosinophil, total-cholesterol, ldl-cholesterol, and triglyceride was significantly higher[(AUC: 0.710 95%CI: 0.60-0.81); Sensitivity=67.6%, Specificity=67.9%, p=0.001]. In the multivariable logistic regression model, only the NIHSS score (National Institutes Of Health Stroke Scale Scores) was independently associated with the degree of disability (p=0.001). NIHSS is an independent factor in predicting stroke outcomes. Conclusion: It was determined that there was a significant inverse relationship between the routine laboratory parameters hemoglobin level, eosinophil level, LDL and total cholesterol levels, and infarct volume with the NIHSS scores of hemoglobin and LDLcholesterol.